Pengaruh Dua Metode Pengeringan Pada Aktivitas Antibakteri Ashitaba (Angelica keiskei ) Terhadap Streptococcus mutans: Effect of Two Different Drying Methods on Antibacterial Activity of Ashitaba Againts Streptococcus mutans - Wirasisya, Dyke Gita; Juliantoni, Yohanes; Hajrin, Wahida (Universitas Tadulako, 2018)
The aim of this study was to determine a change that occurs in total phenolic content (TPC) and antibacterial activity of ashitaba (Angelica keiskei) after dried using two different methods : sun and oven drying. The effectiveness of the drying methods was evaluated in term of total phenolic content (TPC) by using spectrophotometric assay with Folin-Ciocalteu reagent and antibacterial activity againts Streptococcus mutans by in vitro macrodilution assay. Oven drying at 60oC possessed high TPC (2,98 Â± 0,0935 g EAG/100g) compared to sun drying method (1,72 Â± 0,0142 g EAG/100g). Simillar pattern was also observed in antibacterial activity. Oven drying have higher antibacterial activity with the MBC (minimal bactericidal concentration) value of 0,5 mg/mL againts Streptococcus mutans. Therefore, sun drying is not suggested for drying method of ashitaba in terms of total phenolic content and antibacterial activity compared with oven drying methods.